2015
DOI: 10.1007/s00038-015-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in key populations in Latin America and the Caribbean: systematic review and meta-analysis

Abstract: ObjectivesSummarize hepatitis C virus (HCV) prevalence in injecting (IDU) and non-injecting drug users (NIDU), men who have sex with men (MSM), sex workers, and prison inmates in Latin America and the Caribbean (LAC).MethodsSystematic review on HCV prevalence in sub-populations in LAC. Databases searched from 1-1-2000 to 10-30-2013. Inclusion criteria: prevalence studies in sub-populations in LAC. HCV-antibody was marker for prevalence of current/past HCV infection and HCV-RNA for prevalence of HCV current inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 56 publications
(64 reference statements)
0
34
2
3
Order By: Relevance
“…HCV prevalence is nearly universally high among PWID (ranging from 30% to 75% in cohorts in North America, Europe, and Asia [35], and in many high-income countries, active injecting drug use drives ongoing HCV transmission. MSMs (especially those who are HIV infected [36], commercial sex workers and prisoners related to both drug use and perhaps sexual transmission) [37,38], also have increased prevalence.…”
Section: Infection Related To High-risk Behaviours and Populationsmentioning
confidence: 97%
See 2 more Smart Citations
“…HCV prevalence is nearly universally high among PWID (ranging from 30% to 75% in cohorts in North America, Europe, and Asia [35], and in many high-income countries, active injecting drug use drives ongoing HCV transmission. MSMs (especially those who are HIV infected [36], commercial sex workers and prisoners related to both drug use and perhaps sexual transmission) [37,38], also have increased prevalence.…”
Section: Infection Related To High-risk Behaviours and Populationsmentioning
confidence: 97%
“…WHO recommended the use of two main potential testing approaches for HCV infection: focused testing in most affected populations; and birth cohort testing, based on consideration of limited evidence including various systematic reviews on seroprevalence rates in different populations and regions [35][36][37][38][39][40], and a review of costeffectiveness studies of different HCV testing approaches [39,, as well as of programmatic feasibility from reported experience in countries using these approaches [34].…”
Section: Recommendation and Rationale On Testing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in alcohol abusers found 5.6% of anti-HCV in Southeast Brazil [37] and 15% in Southern Brazil [43] what could reflect the diminish in anti-HCV prevalence in this group. The pooled value for HCV prevalence in NIDU was 3.6% (95% CI 2.6-4.5%) [38].…”
Section: Hbv and Hcv Infection In Illicit Substance Usersmentioning
confidence: 94%
“…In Northern Brazil, HBV prevalence (anti-HBc positivity) was 36.7% in ISU, genotypes A, D and F were found and risk factors were: (i) male gender, (ii) age above 35 years, (iii) anti-HIV positivity, (iv) tattoos, (v) the use of injected drugs, (vi) the use of illicit drugs for more than 3 years, (vii) sexual relations without protection, (viii) sexual relations with another DU, and (ix) more than 10 sexual partners in the past 24 months [29]. [38]. Anti-HCV prevalence in ISU was below 7% in the majority of studies included in this review, but anti-HCV rates from 30 to 67% were found in ISU in Argentina and Brazil [39][40][41].…”
Section: Hbv and Hcv Infection In Illicit Substance Usersmentioning
confidence: 99%